Penggunaan Model Cooperative Learning Tipe Picture and Picture sebagai Upaya Meningkatkan Kreativitas dan Hasil Belajar Muatan IPA Peserta Didik di Kelas IV SDN 98/X Rantau Indah Semester Ganjil Tahun Ajaran 2021/2022 - Rosita Rosita (Departement of Mathematics Education, 2022)
This study aims to describe and obtain information on increasing creativity and learning outcomes for science content through the Picture and Picture Cooperative Learning Model. This research is a classroom action research consisting of two cycles, each cycle consisting of two meetings. Each meeting consists of four stages, namely planning, implementation, observation and reflection. The subjects of this study were fourth grade students of SDN 98/X Rantau Indah, totaling 14 people. This research was conducted in the odd semester of the 2021/2022 academic year. Data collection techniques using tests, observations, and documentation. Data were analyzed using percentages. The results showed that through the Picture and Picture Cooperative Learning Model, it could improve the learning outcomes of the fourth grade students of SDN 98/X Rantau Indah science content learning outcomes.